2011
DOI: 10.1039/c1dt10362h
|View full text |Cite
|
Sign up to set email alerts
|

A versatile water soluble fluorescent probe for ratiometric sensing of Hg2+ and bovine serum albumin

Abstract: A novel tetraazamacrocycle fluorescent sensor (6-(1-(dimethylamino)-5-naphthalene sulfonyl)-3,6,9,15-tetraazabicyclo[9.3.1] pentadeca-1(15),11,13-triene, 1) has been designed and prepared, which can be utilized for selective and ratiometric sensing of Hg(2+) and bovine serum albumin (BSA) with two different responsive modes in aqueous solution at physiological pH (50 mM Tris-HCl, pH 7.6). Above 0.5 ppb Hg(2+) can be discerned by coordination with 1 and the emission color changes enable 1 to be applied to a fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…It was later in the spotlight for its ability to form metal complexes [6][7][8], but its wider success was achieved thanks to its utilisation as a scaffold for the preparation of new materials that have proven effective in a variety of applications. Indeed, L derivatives decorated with different hanging functionalities have been studied for several biomedical (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25][26][27] and catalytic [28][29][30][31][32][33] applications. Very recently, (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was later in the spotlight for its ability to form metal complexes [6][7][8], but its wider success was achieved thanks to its utilisation as a scaffold for the preparation of new materials that have proven effective in a variety of applications. Indeed, L derivatives decorated with different hanging functionalities have been studied for several biomedical (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25][26][27] and catalytic [28][29][30][31][32][33] applications. Very recently, (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25]…”
Section: Introductionmentioning
confidence: 99%
“…Anion-π interactions were also found to play an important role in the formation of highly organised polyiodide complexes [44,45] and iodide based permutable organised frameworks (POF) [46] with a pyridinium-based ligand such as Stoddart's blue box (BB, cyclobis(paraquat-p-phenylene)). (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25][26][27] and catalytic [28][29][30][31][32][33] applications. Very recently, it has been shown that L and its N-trimethylated derivative are capable of stabilising iodine-dense three-dimensional networks that might be relevant for crystal engineering purposes and the design of solid-state conductors [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine SA (BSA) has been extensively used in many researches because of the structural homology with human SA [7][8][9]. Several studies have reported the detection of BSA using optical sensors [10][11][12][13]. However, all these researches were performed in solution or plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The perceived colour change would be useful not only for the ra-*Corresponding author, e-mail: jxyang@ahu.edu.cn Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/27/15 5:46 PM tiometric method of detection but also for rapid visual sensing. Although many fluorometric ratiometric probes for Hg 2+ have been developed (Aït-Haddou et al, 2001;Chen & Chen, 2005;Gunnlaugsson et al, 2005;Liang et al, 2007;Guo et al, 2010;Hu & Chen, 2011;Wen et al, 2011), the number of selective and sensitive colorimetric sensors based on the mechanism of internal charge transfer (ICT) available for the detection of Hg 2+ ions in aqueous media remains limited (Sheng et al, 2008;Mei et al, 2012;Shellaiah et al, 2013;Wang et al, 2013). Moreover, many existing colorimetric probes for Hg 2+ are subject to some disadvantages such as complicated synthetic routes, low sensitivity, high cost and lengthy response time.…”
Section: Introductionmentioning
confidence: 99%